Who patents, how much is real invention and how relevant? A snapshot of firms and their inventions based on the 2016 SIPO China Patent Survey - Molnar, Margit (OECD Economics Department Working Papers, 2019)
China has surpassed the United States in patent applications and has become world leader. Strong patenting activity, however, did not lead to strong productivity growth. The delinking of patenting activity from productivity growth could be explained by quality and relevance issues. Although the number of patents has been soaring, few are genuine inventions. Relatively low utilisation rates of patents point to a low degree of relevance. This paper uses a representative survey of Chinese patenting firms to provide a detailed picture of the patenting landscape along the dimensions of geographical areas, detailed industrial sectors, traditional and modern industries as defined by the Chinese government, firm age, size and ownership. It also overviews government subsidies across firms. Transport equipment makers hold most patents per firm, followed by electronics manufacturers.